If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 8y + -9x + -3y = 0 Reorder the terms: 6x + -9x + 8y + -3y = 0 Combine like terms: 6x + -9x = -3x -3x + 8y + -3y = 0 Combine like terms: 8y + -3y = 5y -3x + 5y = 0 Solving -3x + 5y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5y' to each side of the equation. -3x + 5y + -5y = 0 + -5y Combine like terms: 5y + -5y = 0 -3x + 0 = 0 + -5y -3x = 0 + -5y Remove the zero: -3x = -5y Divide each side by '-3'. x = 1.666666667y Simplifying x = 1.666666667y
| 3x+-5+1=19 | | 13.25+.11=14.00-.13 | | (a+2)x^2-2x-a=0 | | Ax-c=-bx+d | | -2x+3=-2x+4 | | 3x+-5+0=19 | | 8(v+2)-2v=3(2v+2)-12 | | 3x+-5-1=19 | | x^2+13=-6x | | 9p^2-5p-3p+22= | | 23.02(X-2.74)=63.72 | | m-32=-16 | | 36+5(-6)-2= | | 54+x+89*3=76 | | 2a^2+5=7 | | 6x+6y=-48 | | 25+9(5)+4= | | -5(-2-a)+5a=-60 | | 4x+20=2x+26 | | 36+8(-6)-9= | | 2.6x+.3x=4+2.3x | | -7(2x+8)=-140 | | 15+30X=10 | | 8n^2+24n+18= | | 10x+5(3x-7)+9(3-2x)=2(2x+5)+15 | | 11+3(8-6x)=17-12x | | 3+5=15+x | | 9-3x=2x+9 | | (7-x)*(3x+9)=0 | | 5x+30x-9=7(5x+3) | | -7x+4y=10 | | 0+6x=11 |